2010
DOI: 10.2188/jea.je20090177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Factors Contributing to Developmental Attainment of Children between 9 and 18 Months

Abstract: BackgroundLittle is known about how contributing factors of development change during early childhood in Japan. The aim of this study was to investigate the factors that contributed to the developmental attainment of children between 9 and 18 months of age using prospective longitudinal data from a developmental cohort study.MethodsWe used data from observations at 3 time points (at infant age of 4, 9 and 18 months) in the Japan Children’s Study. Mothers were administered questionnaires that requested informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…G‐banded chromosomes were normal. The Kinder Infant Developmental Scale [Cheng et al, 2010] showed mild developmental delay with the overall developmental quotient as 65 (physical/motor, 35; manipulation, 58; receptive language, 77; expressive language, 103; conceptual thinking, 77; social relationships with children, 68; social relationships with adults, 116; home training, 68; feeding, 42). He had orchiopexy and a surgical correction of an umbilical hernia at age 2 years and 7 months.…”
Section: Clinical Reportsmentioning
confidence: 99%
“…G‐banded chromosomes were normal. The Kinder Infant Developmental Scale [Cheng et al, 2010] showed mild developmental delay with the overall developmental quotient as 65 (physical/motor, 35; manipulation, 58; receptive language, 77; expressive language, 103; conceptual thinking, 77; social relationships with children, 68; social relationships with adults, 116; home training, 68; feeding, 42). He had orchiopexy and a surgical correction of an umbilical hernia at age 2 years and 7 months.…”
Section: Clinical Reportsmentioning
confidence: 99%
“…1a), respectively. He showed psychomotor delay, with a developmental quotient (DQ) of 57 on the Kinder Infant Development Scale (KIDS) [Cheng et al, 2010]. His craniofacial features included brachycephaly, strabismus, a short nose with anteverted nostrils, a short philtrum, macroglossia, a high palate, a bifid uvula, and a submucous cleft palate.…”
Section: Clinical Reportmentioning
confidence: 99%
“…Only six studies [57][58][59]90,93,98], using respectively DASS, PSI-SF, and Rearing-Related Stress, had a cut-off to indicate threshold of high-level stress. No other studies made any statements regarding cut-off, beyond some stating that 'higher score indicates higher perception of parenting stress'.…”
Section: Plos Onementioning
confidence: 99%